1:1 Alternating Copolymerization of Schiff Bases with Electrophilic Monomers - Annalakshmi, R.; Kavitha, R. (Asian Journal of Chemistry, 2010)
The spontaneous copolymerization of the two Schiff bases p-chlorobenzylidene-1-naphthylamine and p-methoxybenzylidene- 1-naphthylamine with several electrophilic monomers such as succinicanhydride, acryl amide, methacrylic acid, acrylic acid was reported in detail and also characterize them by 1H NMR and IR spectral studies.